Socio-economic determinants of nutritional status of children in rural Peninsular Malaysia - Mohd Marjan, Zamaliah; Mohd Taib, Mohd Nasir; Khor, Geok Lin; Tee, E. Siong (HEC Press, 1998)
The data presented is part of the findings from a four-year collaborative research project between Universiti Putra Malaysia, the Institute for Medical Research and the Ministry of Health Malaysia. The project assessed the nutritional status of the major functional groups in Peninsular Malaysia. Mukim Sayong and Pulau Kemiri in the District of Kuala Kangsar, Perak were two of the subdistricts selected to represent small rubber holdings in Peninsular Malaysia. This paper attempts to analyse the socio-economic profile of the households and the nutritional status of children below 9 years of age. A total of 307 households were studied. Approximately 63% of the households were involved in rubber activities and the majority of them were hired tappers. The average monthly income of the households was RM467 and the income ranged between RM30 to RM2120. Based on the per capita poverty line income of RM84.38, it was found that 14.1% of the households earned less than RM42.19, which can be considered as hard-core poor, while 32.7% were poor (monthly per capita income between RM42.19 and RM84.38). Slightly more than half (52.7%) earned income above the poverty line. The average family size was 4.5, ranging from 1 through to 16. The majority of the heads of households (56.6%) had between 3 and 6 years of education, and 14.5% did not receive any formal education. The prevalence of stunting among children 0-5 years of age was 26%, while 31.5% were underweight and 3.8% wasted. Among children aged between 5 and 9 years, almost the same pattern of nutritional status was noted. The overall percentages of stunting, underweight and wasting among these children were 29.2%, 26.1% and 0.62%, respectively. Analysis on nutritional status according to income level showed a noticeable difference in the prevalence of malnutrition in children above and below the poverty line income. The Student's t-test indicated significant differences in weight-for-age and weight-for-height between the two poverty line income for children below 5 years of age. Pearson's correlation coefficient showed a significant correlation between height-for-age with household size (r = -0.26, P < 0.05), and monthly per capita income with weight-for-height (r = 0.25, P < 0.05). There was a highly significant correlation between acreage of land cultivated and weight-for-height (r = 0.42, P < 0.01), and weight-for-age (r = 0.25, P < 0.05). The findings indicated the influence of socio-economic factors on the nutritional status of children.